Effect of ultrafiltration concentration level of milk and inoculum level on interrelationship between titratable acidity development and pH drop during incubation of dahi - Khurana, Sakshi; Gupta, Dr Vijay Kumar (Indian Journal of Dairy Science, 2014)
The simultaneous effects of ultrafiltration concentration level (UFCL) (1(skim milk), 2, 2.2 and 2.5-fold) and inoculum level (0.3% and 0.5%, v/v) on the acidification process in ultrafiltered (UF) cow milk fermented with dahi culture were investigated. The interrelationship between pH and titratable acidity (TA) changes with change in protein content of milk. Highly significant (p